Pratiques « innovantes », accidents du travail et charge mentale : résultats de l’enquête française « Conditions de travail 1998 » - Philippe Askenazy; Eve Caroli (Perspectives Interdisciplinaires sur le Travail et la Santé)
This paper investigates the impact of innovative workplace practices including job rotation and quality standards on occupational safety and mental strain. It uses a unique French dataset drawn from the 1998 Working Conditions survey, which provides information on individual workers for the year 1998, including data relating to occupational injuries and indicators of mental strain. Using Rubin’s causal model, we show that, even after controlling for employee and job characteristics and correcting for sample selection bias, the workers involved in the new workplace practices still feel they suffer from greater mental strain and more occupational accidents than non-innovative workers.